2020
DOI: 10.1088/1402-4896/abd1b3
|View full text |Cite|
|
Sign up to set email alerts
|

Functional shape effects of nanoparticles on nanofluid suspended in ethylene glycol through Mittage-Leffler approach

Abstract: It is fundamental fact that nanoparticles are strong function of their shapes and sizes; this is because nanoparticles certainly play an adhesive and a significant role in fluid phenomenon. This manuscript investigates the functionality and thermodynamics of different nanoparticles namely gold, alumina, silver and copper suspended in ethylene glycol considered as a base fluid. The problem of mixed convection is modeled by modern fractional derivative by invoking initial and boundary conditions. The analytic ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…where b = 1 1−α and C = s + bα. The velocity distribution for Maxwell fluid can be deduced by implementing λ 2 → 0 and assigning the value of F(s) = 1 s−a in Equation ( 31) the same expression for velocity field is recovered as derived by Imran et al [29].…”
Section: Limiting Casesmentioning
confidence: 99%
See 1 more Smart Citation
“…where b = 1 1−α and C = s + bα. The velocity distribution for Maxwell fluid can be deduced by implementing λ 2 → 0 and assigning the value of F(s) = 1 s−a in Equation ( 31) the same expression for velocity field is recovered as derived by Imran et al [29].…”
Section: Limiting Casesmentioning
confidence: 99%
“…Finite Fourier sine transform, Laplace, and fractional techniques have been utilized to the governing equations for exhibiting typical and rheological properties of the problem. Although the studies on heat and transfer analysis can be continue yet the relevant studies can be observed therein in categorical format as heat transfer via analytical approaches [16][17][18][19][20][21][22][23], heat transfer via numerical approaches [24][25][26][27][28][29], heat transfer via fractional calculus approaches [30][31][32][33], and heat transfer via multi-dimensional approaches [34][35][36][37]. Motivating by the above consideration, the main theme of this manuscript is to have the significance of convective heating and variable heat source on Azimuthal oscillatory MHD convective flows developed in a cylindrical Darcy-Forchheimer porous medium filled by a radiating second-grade fluid.…”
Section: Introductionmentioning
confidence: 99%
“…Sodium alginate natural convection based Fe 2 O 3 -nanofluid with accretion/ ablation was illustrated by Hussanan et al [34]. The mixed convection ethylene glycol based nanofluids flow, together with the functional shape effects of nanoparticles was investigated by Memon et al [35]. Hussanan et al [36] highlighted the impacts of magnetic and non-magnetic nanoparticles on viscoplastic Casson-based mixture hybrid nanofluid.…”
Section: Introductionmentioning
confidence: 99%
“…A finite Fourier sine transform, Laplace and fractional techniques were applied to the governing equations to show the typical and rheological properties of the problem. Although the studies on heat and transfer analysis will be continued the relevant studies can be observed therein in categorical format as: heat transfer via analytical approaches [16,17,[29][30][31][32], heat transfer via numerical approaches [18,19,[33][34][35][36], heat transfer via fractional calculus approaches [20,21,37,38] and heat transfer via multidimensional approaches [22,23,25,26,39,40]. Motivated by the above consideration, the main theme of this paper is to assess the significance of convective heating and variable heat source on the azimuthal oscilatroy MHD convective flows developed in a cylindrical Darcy-Forchheimer porous medium filled by a radiating second-grade fluid.…”
Section: Introductionmentioning
confidence: 99%